Inglés Básico - Montiel Lira, Diana (My University, 2004)
ÍNDICE 1. Saludos 2. Información 3. Información laboral 4. Propiedad 5. Dudas 6. Familia 7. Vocabulario 8. Gramática
Keywords: Inglés básico; Nice meeting you, nice to meet you, great to meet you all, what´s your name and address?, what´s your telephone number?, where are you from?, what do you do for a living?, what about you?, their, my, Jose´s book, your, John´s copy, guess, present progressive, how old are they?, nouns, adjectives